Contributions of an Augmented Reality Musical System for the Stimulation of Motor Skills in Music Therapy Sessions - Corrêa, Ana Grasielle Dionísio; Ficheman, Irene Karaguilla; Nascimento, Marilena do; Lopes, Roseli de Deus (IntechOpen, 2012)
None